Challenges of Online Teaching in Rural Area: What Have They Learned for Teacher Development? - Pratiwi, Andiany Retno; Lengkanawati, Nenden Sri (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
This study explored the perceived challenges of online learning encountered by teachers in rural areas. The students and teachers in rural areas often need more facilities and expertise to implement online education. This research's primary purpose is to examine the teacher's challenges and the impact of online learning on teachers' development in rural areas. Qualitative descriptive research is used as a research design to explore phenomena. Data were collected through interviews and participant observation and then analyzed using the data analysis thematic analysis (Creswell Poth, 2018). The findings show that the teachers used technology to ensure the continuity of online learning. However, inadequate infrastructures, internet connections, and poor digital skills become the central problems in online learning. Thus, all stakeholders, such as teachers, students, parents, and the government, must adopt technology and improve their digital skills. Moreover, for the development of teachers, workshops, webinars, and so on are needed to facilitate, increase and enable teachers to make competent use of online learning as the teachers develop learning strategies in online education during Covid-19 and beyond. Keywords: Teacher professional development, online learning, teacher development